Effect of Novel Fast Heating Processing Route on the Formation of Martensitic Microstructures and the Subsequent Impact on Mechanical Properties of 0.2–0.3%C Steels for Abrasion-Resistant Plates - Castro-Cerda, F; Carreño-Saavedra, J (Association for Iron and Steel Technology, 2025)
[No abstract available]